Peptides from conserved regions of paramyxovirus fusion (F) proteins are potent inhibitors of viral fusion. - Lambert, D M (1996)
The synthetic peptides DP-107 and DP-178 (T-20), derived from separate domains within the human immunodeficiency virus type 1 (HIV-1) transmembrane (TM) protein, gp4l, are stable and potent inhibitors of HIV-1 infection and fusion. Using a computer searching strategy (computerized antiviral searching technology, C.A.S.T.) based on the predicted secondary structure of DP-107 and DP-178 (T-20), we have identified conserved heptad repeat domains analogous to the DP-107 and DP-178 regions of HIV-1 gp41 within the glycoproteins of other fusogenic viruses. Here we report on antiviral peptides derived from three representative paramyxoviruses, respiratory syncytial virus (RSV), human parainfluenza virus type 3 (HPIV-3), and measles virus (MV). We screened crude preparations of synthetic 35-residue peptides, scanning the DP-178-like domains, in antiviral assays. Peptide preparations demonstrating antiviral activity were purified and tested for their ability to block syncytium formation. Representative DP-178-like peptides from each paramyxovirus blocked homologous virus-mediated syncytium formation and exhibited EC50 values in the range 0.015-0.250 microM. Moreover, these peptides were highly selective for the virus of origin. Identification of biologically active peptides derived from domains within paramyxovirus F1 proteins analogous to the DP-178 domain of HIV-1 gp4l is compelling evidence for equivalent structural and functional features between retroviral and paramyxoviral fusion proteins. These antiviral peptides provide a novel approach to the development of targeted therapies for paramyxovirus infections.